2016
DOI: 10.1116/1.4972858
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-enhanced atomic layer deposition of superconducting niobium nitride

Abstract: Thin films of niobium nitride are useful for their physical, chemical, and electrical properties. NbN superconducting properties have been utilized in a wide range of applications. Plasma-enhanced atomic layer deposition (PEALD) of NbN with (t-butylimido) tris(diethylamido) niobium(V) and remote H2/N2 plasmas has been investigated. Deposited film properties have been studied as a function of substrate temperature (100–300 °C), plasma power (150–300 W), and H2 flow rate (10–80 sccm). PEALD NbN films were charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
22
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
6
22
1
Order By: Relevance
“…The inset also shows that our films follow a universal relation observed for thin superconducting films [29] linking T c , film thickness t, and sheet resistance R : we find that our results are similar to NbN deposited with other methods [29,31]. For thicker films, T c appears to saturate at 13.8-13.9 K which is comparable to other materials studies [29,30,32], while decreasing to 8.7 K for the thinnest film (t=7 nm), which can be attributed to disorder enhanced Coulomb repulsions [35,36]. We also find that the superconducting transition width increases significantly for the thinner films, which can in turn be attributed to disorder broadened density of states [36] or reduced vortexantivortex pairing energies at the transition [33,37].…”
supporting
confidence: 89%
See 2 more Smart Citations
“…The inset also shows that our films follow a universal relation observed for thin superconducting films [29] linking T c , film thickness t, and sheet resistance R : we find that our results are similar to NbN deposited with other methods [29,31]. For thicker films, T c appears to saturate at 13.8-13.9 K which is comparable to other materials studies [29,30,32], while decreasing to 8.7 K for the thinnest film (t=7 nm), which can be attributed to disorder enhanced Coulomb repulsions [35,36]. We also find that the superconducting transition width increases significantly for the thinner films, which can in turn be attributed to disorder broadened density of states [36] or reduced vortexantivortex pairing energies at the transition [33,37].…”
supporting
confidence: 89%
“…[32]. (t-Butylimido)Tris(Diethylamido)-Niobium(V) (TBTDEN) was used as the niobium precursor, which was kept at 100 • C and delivered by a precursor Boost TM system, which introduces argon gas into the precursor cylinder to promote material transfer of the low vapor pressure precursor to the wafer [32]. The deposition cycle consisted of three 0.5 second pulses of boosted TBTDEN followed by 40 seconds of 300 W plasma consisting of 80 sccm hydrogen and 5 sccm nitrogen.…”
Section: Appendix B: Device Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, previously, it has been demonstrated that usage of the metalorganic precursor ( t BuN)2(Me2N)2W along with N2, H2/N2 and NH3 plasmas for a WNx ALD process have resulted in very low levels of carbon impurities (<2 at.%). 32 Here, we provide a detailed study on the tungsten trioxide ALD process and the material properties of the as-deposited material. The influence of deposition temperature on GPC, chemical composition, stoichiometry and optical properties of the resulting WO3 films is investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The best results combining the highest T c as well as the lowest resistivity are achieved at the substrate temperature of 300 • C and 300 W plasma power. More details on the preparation process including other optimized parameters could be found in Ref 47 . Figure 1(a) plots the measured NbN film thickness with respect to the number of deposition cycles.…”
mentioning
confidence: 99%